Characterization of a cDNA Encoding Murine Coagulation Factor VII - Idusogie, Esohe; Rosen, Elliot; Geng, Jie-Ping; Carmeliet, Peter; Collen, Desirá; Castellino, Francis J (Thrombosis and Haemostasis, 1996)
The cDNA encoding murine coagulation factor VII (mfVII) was isolated and reconstructed from a Λ Zap cDNA library generated from murine liver mRNA. The cDNA contains 1903 nucleotides spanning 15 bases upstream of the 5’-translation initiation codon, an open reading frame of 1338 nucleotides, 550 nucleotides downstream of the first stop codon and a 3’ poly(A) tail. The translation product is composed of a 41-amino acid signal/propeptide region followed by a 405-residue mature protein. The latter is highly homologous to that of human, rabbit, bovine, Rhesus monkey, and canine fVII. All protein domains of hfVII are strictly conserved in mfVII.